Math, asked by kabiragg69, 6 months ago

Find : S(tan x - cotx) dx
dx.​

Answers

Answered by Anonymous
3

Answer:

∫  

tanx

​  

+  

cotx

​  

dx=∫  

cosx

​  

 

sinx

​  

 

​  

+  

sinx

​  

 

cosx

​  

 

​  

dx

∫  

sinxcosx

​  

 

sinx+cosx

​  

dx=  

2

​  

∫  

2sinxcosx

​  

 

sinx+cosx

​  

dx

=  

2

​  

∫  

2sinxcosx+1−1

​  

 

sinx+cosx

​  

dx=  

2

​  

∫  

1−(sinx−cosx)  

2

 

​  

 

sinx+cosx

​  

dx

put sinx−cosx=t (sinx+cosx)=dt

=  

2

​  

∫  

1−t  

2

 

​  

 

dt

​  

=  

2

​  

sin  

−1

t+c

=  

2

​  

sin  

−1

(sinx−cosx)+c

D is correct.

Step-by-step explanation:

Similar questions